Long-Term Neurologic Consequences following Fetal Growth Restriction: The Impact on Brain Reserve - Shah, Divyen K.; Pereira, Susana; Lodygensky, Gregory A. (Developmental neuroscience, 2025)
Abstract Background: Fetal growth restriction (FGR) corresponds to the fetus’s inability to achieve an adequate weight gain based on genetic potential and gestational age. It is an important cause of morbidity and mortality. Summary: In this review, we address the challenges of diagnosis and classification of FGR. We review how chronic fetal hypoxia impacts brain development. We describe recent advances on placental and fetal brain imaging using magnetic resonance imaging and how they offer new noninvasive means to study growth restriction in humans. We go on to review the impact of FGR on brain integrity in the neonatal period, later childhood, and adulthood and review available therapies. Key Messages: FGR consequences are not limited to the perinatal period. We hypothesize that impaired brain reserve, as defined by structure and size, may predict some concerning epidemiological data of impaired cognitive outcomes and dementia with aging in this group of patients. Background: Fetal growth restriction (FGR) corresponds to the fetus’s inability to achieve an adequate weight gain based on genetic potential and gestational age. It is an important cause of morbidity and mortality. Summary: In this review, we address the challenges of diagnosis and classification of FGR. We review how chronic fetal hypoxia impacts brain development. We describe recent advances on placental and fetal brain imaging using magnetic resonance imaging and how they offer new noninvasive means to study growth restriction in humans. We go on to review the impact of FGR on brain integrity in the neonatal period, later childhood, and adulthood and review available therapies. Key Messages: FGR consequences are not limited to the perinatal period. We hypothesize that impaired brain reserve, as defined by structure and size, may predict some concerning epidemiological data of impaired cognitive outcomes and dementia with aging in this group of patients.